Constructing Trust in Phishing Emails: A Corpus-Assisted Discourse Analysis of Lexical and Persuasive Strategies - Marrium Sayyed (Policy Journal of Social Science Review, 2026)
Using Sketch Engine's Word Sketch, Word Sketch Difference, Concordance, and Wordlist features, this study aims to identify how trust is linguistically constructed in phishing emails. Guided by Mayer, Davis, and Schoorman's (1995) Integrative Model of Organizational Trust, Halliday's Systemic Functional Linguistics, and Cialdini's Principles of Persuasion, the analysis identifies how a small set of recurring lexical and grammatical choices work together to project competence (Ability), care for the recipient (Benevolence), and legitimacy (Integrity). For example, the noun authority collocates most strongly with reassurance and urgency; the lemma urgency consistently co-occurs with authority and reassurance across the dataset. The analysis also shows how urgency-marked directives, hedged modality, and service-oriented reassurance combine to produce a compact yet internally coherent trust-building schema, consistent with patterns reported in prior research on phishing linguistics and persuasion. Keywords: Emails, Trust, Corpus, Sketch Engine, Ability, Integrity, Benevolence. https://doi.org/10.5281/zenodo.21848709